Estimación de costos del proceso de atención del infarto agudo de miocardio ST elevado en el Hospital Nacional Edgardo Rebagliati Martins enero-diciembre 2016 - Rios Navarro, Patricia (2020)
Objective: To estimate the resources used and costs of care of ST elevation acute myocardial infarction (AMI), in the cardiology department of the Edgardo Rebagliati Martins National Hospital (HNERM) during 2016, , according to the institution´s perspective. Method: Quantitative, descriptive, cross-sectional study. Considering the length of hospital stay, the procedures performed and the medications indicated, the costs of care were assessed, grouping the patients according to the presence of complications or the indication for coronary artery bypass graft surgery (CABG). Results: The cost derived from the use of resources for the care of ST elvation AMI without complications and without indication of CABG was S /. 15 142.05 ($ 4486.53), with an average stay of 8.2 days; with the addition of medical complications or MACE, the stay was prolonged by 50%. In the group of patients with ST elevation AMI and indication of CABG, the cost derived from the use of resources was S /. 25 877.02 ($ 7667.27), with an average stay of 42.2 days, which lasted 45% if medical complications or MACE occurred. Conclusion: Excluding the groups that had indication of CABG, the highest proportion of the cost was related to the procedures applied for the treatment of ST elevation AMI. In the group of patients who underwent surgery, the highest proportion of the cost was in the hospital stay.